A review on liquid chromatography-tandem mass spectrometry methods for rapid quantification of oncology drugs - Wong, A.; Xiang, X.; Ong, P.; Mitchell, E.; Syn, N.; Wee, I.; Kumar, Alan Prem; Yong, W.; Sethi, G.; Goh, B.; Ho, P.; Wang, L. (MDPIAG, 2018)
In the last decade, the tremendous improvement in the sensitivity and also affordability of liquid chromatography-tandem mass spectrometry (LC-MS/MS) has revolutionized its application in pharmaceutical analysis, resulting in widespread employment of LC-MS/MS in determining pharmaceutical compounds, including anticancer drugs in pharmaceutical research and also industries. Currently, LC-MS/MS has been widely used to quantify small molecule oncology drugs in various biological matrices to support preclinical and clinical pharmacokinetic studies in R&D of oncology drugs. This mini-review article will describe the state-of-the-art LC-MS/MS and its application in rapid quantification of small molecule anticancer drugs. In addition, efforts have also been made in this review to address several key aspects in the development of rapid LC-MS/MS methods, including sample preparation, chromatographic separation, and matrix effect evaluation.